Tahlil Kitab Ta’lim Al-Lughah Al-‘Arabiyyah Al-Ladziy Allafahu Al-Duktur Hidayat - M. Kamil Ramma Oensyar; Nur Amalia (Rumah Jurnal IAIN Bukittinggi, 2021)
Textbooks are a very important component in the learning process. The researcher conducts an analysis here using the theory of Rusydi Ahmad Thu'aimah in his book Manahij Tadris Al-lughah Al-Arabiyyah Bi-ta'lim Al-asasi about the criteria for writing Arabic books for elementary third graders. The results of the study explain that: Dars (1) regarding